Fast flexible power point tracking and grid support in photovoltaic power plants - Narang, Aditi (2019)
With an imperious demand in clean power generation based on renewable sources, there is an increase in penetration of solar based energy systems more than ever. Flexible power point tracking (FPPT) is the mechanism to regulate the active power produced by grid-connected photovoltaic power plants (GCPVPPs) to provide various grid-support functionalities. An adaptive control scheme for FPPT operation in GCPVPPs was previously introduced, which uses adaptive algorithm for calculating the voltage-step and voltage-reference values based on the current operational conditions. The main aim was to achieve fast response during transient and reduced power oscillations in steady-state. However, the transient response of the procedure was limited by the bandwidth of the dc-dc converter controller. To enhance the transient performance, a dynamic voltage reference design is introduced. The application of the dynamic voltage reference design for the FPPT operation has several advantages including higher bandwidth, flexibility for adaptation of constraints/saturation based on the operation conditions and lack of complex tuning requirements. A model predictive control technique is also implemented to regulate the average inductor current, to the reference value calculated by the dynamic voltage reference design algorithm. Experimental results have been presented to illustrate the efficacy of the proposed algorithm when subjected to rapid changes in PV voltage and power reference changes. Inverter controller regulates the dc-link voltage to its reference by calculating the current reference in the direct axis of the d-q frame. The quadrature current of the d-q frame is calculated so as to compensate for grid voltage sags by injecting reactive power into the grid. Power reserve function or frequency support is achieved by keeping a reserve of 10%-20% of the available maximum power. In case there is a sudden reduction in frequency, the reserve power can be used to send active power into the ac grid. Similarly, in case there is an increase in frequency, injected active power into the grid is reduced.